Resíduos sólidos e as tecnologias: uma proposta para sensibilização e engajamento de uma comunidade escolar - Castione, Regiane Cristina Mareze Sipione (2022)
The National Solid Waste Policy (PNRS) in Brazil was instituted by Law No. 12,305, of August 2, 2010, and regulated by Decree No. 7,404, of December 23, 2010, in order to establish instruments for the management and management of solid waste. States and Municipalities had to comply with this legislation and make their Solid Waste Management Plans (PGRS). The municipality of Foz do Iguaçu/PR/BR launched in 2015 a pilot project in the northern region of the city that comprised in 25 (twenty-five) neighborhoods and 15 (fifteen) educational institutions for the implementation of the PGRS, among them the State College Professor Flávio Warken Middle and Vocational Elementary School. Over the years, it was found that the operationalization process of the PGRS presented some failures, which can be generated by the high turnover of teachers, students, and employees. The objective of this research was to seek technological alternatives to raise awareness and engagement of the school community (students) for the operationalization of the PGRS in public schools and answer the question: What are the contributions of gamification, to sensitize and engage a school community, in the operationalization of solid waste management, in a public school in Foz do Iguaçu? Therefore, as a methodological strategy, a game-winning short course was elaborated for students using free technological tools. The results obtained showed us that the activity was motivating, engaging, sensitizing and stimulated the participants to develop a game to play with the school community, which can contribute to the operationalization of the PGRS.